PENINGKATAN LITERASI DIGITAL SISWA DI MIN 11 BANDA ACEH MELALUI PERAN AKTIF GURU DALAM MENERAPKAN TEKNOLOGI INFORMASI SEBAGAI SARANA PEMBELAJARAN EFEKTIF - Silfia Ikhlas; Sri Suyanta (Program Studi Manajemen Pendidikan Islam, 2024)
Increasing digital literacy is an important component in preparing students to face the increasingly rapid development of technology. This study aims to analyze the active role of teachers in utilizing information technology as an effective learning tool at MIN 11 Banda Aceh. The research method used is a qualitative approach with a descriptive design to reveal the application of information technology by teachers in improving students' digital literacy. The findings of the study indicate that teachers at MIN 11 Banda Aceh proactively utilize various technological devices, such as computers, tablets, and digital learning applications in teaching and learning activities. In addition, teachers also provide students with supplies on how to use technology appropriately and efficiently. The application of this technology not only improves students' ability to access and evaluate information but also helps develop critical thinking skills, collaboration, and creativity. Despite challenges related to infrastructure limitations and differences in technological abilities among students, teachers are able to overcome these obstacles with innovative solutions. Overall, this study shows that the active role of teachers in integrating information technology into the learning process greatly contributes to improving students' digital literacy, which is very important in today's digital era.